Augmented reality applied to museology (Cadernos de Sociomuseologia, 2015)
This thesis focuses on the relationship between the visitor/participant and the museological installations. It is assumed that the main objective of a museological installation is to promote the creation of knowledge. In this sense, we explore a number of different exhibition resources, in particular Augmented Reality that enables different readings of the same element/object, and, in this way, it extends the set of possible interactions.For the production and development of museological installations, we have in consideration an iterative design process, combined with an evaluation in the wild, in order to develop the installations in accordance with the visitor’s feedback and verifying if the proposed objectives are being achieved.At the Petrie Museum of Egyptian Archaeology we have developed an installation based on gesture tracking, and focused research in an iterative process; on the other hand at the exhibition Baixa in Real Time, although we have implemented a few changes based on the visitor’s feedback we have focused on identifying different patterns of interaction while interacting with specific installations.In this sense, it is understood that the museological installations can be developed collaboratively, where it is taken into account the different actors in this process, as the visitors/participants, the stakeholders, the technicians, the designers or the museologists.Through the development of museological installations in a dynamic way, participative and in constant update, means to be closest to produce installations that respond to their main objective. Key-words: Augmented Reality, Museology, Expography, Museological Installation